Associations between vitamin D, immunoglobulin E concentrations, and obesity - Avila Castillo, Angelica; Hagemann, Tobias; Hoffmann, Anne; Baber, Ronny; Biemann, Ronald; Wirkner, Kerstin; Krupka, Sontje; Stumvoll, Michael; Blüher, Matthias; Klöting, Nora (Frontiers in Nutrition, 2023)
The prevalence of allergies and obesity has been increased in parallel. Low vitamin D (25(OH)D) levels have been linked to both higher body mass index (BMI) and allergies. Since the activation of the 25(OH)D receptor inhibits IgE production and 25(OH)D influences the IgE response specifically, we tested the hypothesis that circulating 25(OH)D concentrations are negatively related to circulating allergen-specific IgE concentrations distinctly in a large adult population-based study cohort. Moreover, we studied VDR gene expression in paired biopsies of abdominal subcutaneous (SAT) and visceral adipose tissue (VAT). We investigated whether magnetic resonance imaging-estimated visceral (VFM) and subcutaneous fat mass (SFM) are related to 25(OH)D levels. We found gender differences in circulating 25(OH)D and IgE concentrations. Participants with obesity showed lower 25(OH)D concentrations and higher IgE concentrations were detected in women only. Interestingly, participants with high levels of 25(OH)D are leaner and have improved glucose metabolism. In women, 25(OH)D correlate significant with VFM and SFM. VDR expression is significantly higher expressed in VAT and is positive associated with circulating 25(OH)D concentration. There was no association between serum IgE and 25(OH)D in the entire cohort. Based on these data, we could confirm that low levels of 25(OH)D are linked to higher BMI but could not prove our hypothesis because there is no relationship between 25(OH)D and IgE in adults. Women with higher BMI tend to have higher IgE levels what may have clinical relevance. The association between obesity and circulating 25(OH)D/IgE is not straightforward, and further knowledge is needed.